P25 15 year retrospective study of non-tuberculous mycobacteria (NTM) isolates. (19th November 2012) - Scadding, AJ; Ohri, C; Perera, N; Woltmann, G
Abstract : Introduction: The incidence non-tuberculous mycobacteria (NTM) has been growing steadily and was previously estimated between 2.9–4.43/100, 000 persons. 125 NTM species have been identified due to advances in laboratory techniques with a corresponding increase of clinical presentations. Treatment is recommended if the same species is cultured on at least 2 occasions with clinical/radiological evidence for progression. Other than cystic fibrosis predisposing factors in adults include chronic lung disease, immunodeficiency, gastro-oesophageal reflux disease and post-menopausal non-smoking females.[1] Methods: 768 isolates were collected over 15 years in our regional mycobacterial database and analysed for demographic and frequency distributions using simple statistics. The data includes many single, incidental isolates as well as patients with multiple isolates and on-going symptoms. Results: We analysed 768 non-tuberculous mycobacterial cultures from 534 patients. The mean age for first positive culture was 55 (range 0–102) with 42.7% of the isolates occurring above age 65. 58% (310) of subjects were male, 61.3% were white Caucasian and 24.5% were of South Asian ethnicity. 81.4% of isolates were single with only 2% of patients culturing more than 4 isolates. The patient with most isolates (12) grew Mycobacterium Avium Complex (MAC) repeatedly over a 10-year time span. The most common isolate was MAC (37.0%) followed by the rapidly growing mycobacteria (RGM) which accounted for 28.4%. In descending order M. Kansasii, M. Gordonae and M. Xenopi accounted for 8.7%, 6.9% and 3.9% of the isolates respectively. The majority of cultures were of respiratory origin from sputum (76.2%) and broncho-alveolar lavage (7%) samples. 3.8% of samples were cultured from pus, 1.3% from blood cultures and 0.7% from lymph nodes. Discussion: In keeping with previous studies MAC was the most commonly identified mycobacterium and the most common population were older, white peoples. Our data for culture site compares to that published by the American Centers for Disease Control and Prevention. Our data highlights that a variety of NTM can be isolated from multiple locations and pose a diagnostic challenge. DE Griffith et al., "An Official ATS/IDSA Statement: Diagnosis, Treatment, and Prevention of Nontuberculous Mycobacterial Diseases, " AJRCCM 175, no.4 (February 2007): 367–416.